Biomass, Productivity and Nutrient Cycling in a Dalbergia sissoo Plantation - Sharma, D. C.; Taneja, P. L.; Bisht, A. P. S. (Indian Forester, 1988)
The biomass, prductivity and nutrient cycling in a 24 year old Dalbergia sissoo plantation have been discussed in this paper. Out of the total above-ground biomass of 162 metric tonnes/ha the roots contribute 15.4 per cent. Maximum concentration of nitrogen was observed in leaf and minimum in the bole. The highest concentration of calcium was found in bark and least in the bole. As compared with the annual uptake of nutrients, 63 per cent N, 50 per cent P, 48 per cent K, 67 per cent Ca and 57 per cent of Mg are returned to the soil annually through litter fall.